Switching therapy in patients with age-related macular degeneration, diabetic macular edema and cistoid macular edema due to retinal vein occlusion - Dijana Risimić; Jelena Karadžić; Miroslav Jeremić; Nada Avram (Биомедицинска истраживања, 2019)
Introduction: Intravitreal injection of anti-vascular endothelial growth factor (VEGF) agents has revolutionized the management of age-related macular degeneration (AMD), diabetic macular edema (DME), macular edema in retinal vein occlusions (RVO), and other retinal diseases accompanied by neovascular and macular edema. The aim of the study is to show the efect of switching from bevacizumab to alibercept in patients with recalcitrant wet AMD as the best clinical approach and regimen for patients with neovascular and macular edema accompanied retinal diseases. Methods: All our patients received the intravitreal injections of 1.25 mg (0.1 mL) bevacizumab as the irst treatment option, and we switched to alibercept or triamcinolon acetonid when the therapy including bevacizumab seemed not to be efective enough, according to visual acuity and optical coherent tomography (OCT) indings. Case presentations. We presented four cases: two patients with wet AMD, one patient with macular edema due to central retinal vein occlusion (CRVO) and one patient with DME in non-proliferative diabetic retinopathy (nPDR). The majority of our patients felt visual and anatomical improvement. Some patients felt anatomical improvement although their visual acuity did not improve. Switch to alibercept had prolonged the positive efect of bavacizumab for approximately 2 months. When regular therapy including bevacizumab was reintroduced, the therapeutic efect would be prolonged. The efective clinical approach was not only the switching therapy but the combination therapy as well. Individual treatment approach and pro re nata regimen were most commonly used in our patients. Conclusion: Switching anti-VEGF drug showed positive results in patients with refractory or recurrent wet AMD and macular edema.
Keywords: vascular endothelial growth factor agents; wet age-related macular degeneration; macular edema; switching therapy